18F‐fluoro‐2‐deoxy‐2‐d‐glucose PET‐CT (FDG PET‐CT) in staging of high‐risk renal and urothelial bladder cancers (COPPER‐T) trial protocol - Rahul Jena; Priyank Bhargava; Shashank Tripathi; Sameer Taywade; Taruna Yadav; Arjun Singh Sandhu; Mahendra Singh; Shiv Charan Navriya; Deepak Prakash Bhirud; Amit Aggarwal; Gautam Ram Choudhary (BJUI Compass, 2023)
Abstract Background and Study Design Role of 18F‐fluoro‐2‐deoxy‐2‐d‐glucose positron emission tomography‐computed tomography (FDG PET‐CT) in evaluation of renal cell cancers (RCC) and urinary bladder cancers is not standardized, and the COPPER‐T trial, which is a single centre prospective randomized study, was designed to compare it with conventional imaging for staging of clinically localized high risk RCC and urinary bladder carcinoma (Stage T2 and above). Patients and Methods There will be two subgroups of patients: RCC and urinary bladder carcinoma. In each of these, the patients will be randomized to either Arm A or Arm B. In each of the arms, each patient will be subjected to diagnostic imaging by FDG PET‐CT. The CT scan will be a contrast‐enhanced scan like that in conventional staging. A radiologist and nuclear medicine specialist will report the scan independently. The radiologist will not have access to the PET scan sequences and will only review the contrast‐enhanced computed tomography (CECT) images. In Arm A, the report of the conventional imaging modality, that is, CECT and bone scan if done, will be reviewed first by the clinician, and based on this report, a management plan will be made. Then, the PET‐CT report will be reviewed, and change in the management plan will be noted. New findings or equivocal findings if any in the PET‐CT report would be noted. In Arm B, the report of the PET‐CT report will be reviewed first by the clinicians, and a management plan will be made. Then, the CECT and/or bone scan reports will be reviewed, and any change in the management plan will be noted. Outcome and Significance Final analysis of the data after completion of the trial will help in clarifying the role of FDG PET‐CT in high risk RCC and transitional cell carcinoma (TCC) of the bladder, its diagnostic accuracy compared with conventional imaging and the impact of using it on patient management.